SIYASAH SYAR’IYAH DALAM PELAKSANAAN UNDANG-UNDANG JENAYAH ISLAM - Abd Majid, Mahmood Zuhdi (Jurnal Syariah, 2019)
Siyasah Syar'iyah is a significant concept in Islamic governance. From the other perspective, Siyasah Syar'iyah is defined as a method of lJukm detennination which is based on public interest without any contradiction with any Islamic principles. This article discusses the implementation of Siyasah Syar'iyah in detennining lJukm and solving problem during Islamic Sultanate by bringing several practicle examples. It is important to be revealed, so that the contemporary ulama can use it as a guideline to solve the current issues.